Case Report: Multiple types of arrhythmias in a late-confirmed Danon disease - Wang, Nan; Cao, Yu; Wang, Jie; Zhang, Qing (Frontiers in Cardiovascular Medicine, 2024)
Introduction Danon disease is an X-linked disorder caused by pathogenic variants in lysosome-associated membrane protein 2 (LAMP2) gene, typically characterized by the triad of hypertrophic cardiomyopathy, myopathy, and intellectual disability. However, many patients may not present the typical presentation, especially in the early stage. Electrocardiogram (ECG) abnormalities can be found in almost all patients, with Wolff–Parkinson–White (WPW) syndrome being the most common. We reported the case of a 51-year-old woman who experienced multiple types of arrhythmias over three decades and was diagnosed with Danon disease late by genetic testing. Case summary A 51-year-old woman with a 36-year history of intermittent palpitations was admitted due to hemodynamically stable ventricular tachycardia (VT). Her past medical history revealed multiple arrhythmias and ECG abnormalities in her 30s and 40s, including WPW syndrome with paroxysmal supraventricular tachycardia, paroxysmal atrial flutter, atrial fibrillation, ventricular tachycardia, and complete left bundle branch block. She denied any family history of cardiovascular disease or sudden death. Upon arrival, her vital signs were unremarkable. Cardiovascular magnetic resonance (CMR) imaging revealed left ventricular enlargement and late gadolinium enhancement (LGE) in the anterior, inferior, and lateral walls. Subsequent, whole-exome sequencing (WES) gene testing revealed a pathogenic heterozygous variant in LAMP2 gene (c.696T>A; p.Cys232Ter), which confirmed the diagnosis of Danon disease. Conclusion Genetic testing should be considered in patients who display multiple arrhythmias with LV structural abnormalities of unknown etiology for a possible Danon disease.